Pembinaan Keagamaan DKM Masjid Miftahul Huda dalam Meningkatkan Kesadaran Salat berjamaah di Kalangan Pemuda - Elvin Muhib Qolbin Salim; Komarudin Shaleh; Hendi Suhendi (UNISBA Press, 2024)
Abstract. Religious formation is a form of effort to foster and train individual religion to achieve the expected goals. So efforts to increase youth awareness must be structured in a structured and targeted activity program. The author conducted this research with the aim of: finding out the religious guidance of the DKM Miftahul Huda Mosque in increasing awareness of congregational prayer among youth. This research focused on the problem formulation (1) how the religious guidance program works, (2) what the results of religious guidance are (3) how youth awareness at the DKM Miftahul Huda mosque in carrying out congregational prayers. The theory used in this research: Djamaludin Ancok's theory (1994) in the book